2012
DOI: 10.1021/ja300684r
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Dehydrogenative β′-Functionalization of β-Keto Esters with Indoles at Room Temperature

Abstract: The dehydrogenative β'-functionalization of α-substituted β-keto esters with indoles proceeds with high regioselectivities (C3-selective for the indole partner and β'-selective for the β-keto ester) and good yields under mild palladium catalysis at room temperature with a variety of oxidants. Two possible mechanisms involving either late or early involvement of indole are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Although the above experiments established that enone 4a is indeed a viable intermediate for the reaction, control experiments without indole 2a clearly demonstrated that enone formation is very slow in the absence of indole. 5 The reaction progress method allowed us to obtain kinetic isotope effect (KIE) data for all key reaction components, using deuteriumlabeled starting materials. 12 The first KIE experiment involved a comparison of C2-H vs C2-D-labeled indole (Figure 2 a).…”
Section: Scheme 3 Reactions Of Indole 2a and Enone 4amentioning
confidence: 99%
“…Although the above experiments established that enone 4a is indeed a viable intermediate for the reaction, control experiments without indole 2a clearly demonstrated that enone formation is very slow in the absence of indole. 5 The reaction progress method allowed us to obtain kinetic isotope effect (KIE) data for all key reaction components, using deuteriumlabeled starting materials. 12 The first KIE experiment involved a comparison of C2-H vs C2-D-labeled indole (Figure 2 a).…”
Section: Scheme 3 Reactions Of Indole 2a and Enone 4amentioning
confidence: 99%
“…Although the study of such reactivity has delivered many useful transformations, this chemistry requires substrates that are not as widely available or require an additional preoxidation step from a saturated precursor (59). Previous studies in transition metal catalysis have shown that direct β-functionalization of esters or amides is possible through the use of palladium catalysis, albeit with only a few examples known to date (1013). A direct aldehyde or ketone β-coupling mechanism would obviate the need for preactivated substrates.…”
mentioning
confidence: 99%
“…Drawing from the mechanistic insights gained in the course of our β-arylation program, 1a we envisioned a direct β-coupling of saturated ketones with aryl–alkyl and diaryl ketone precursors. Specifically, we postulated that a transiently formed nucleophilic β-enaminyl 5πe − species ( 1 ) would be intercepted by a ketyl radical ( 2 ) to directly form a γ-hydroxyketone adduct (Eq 2).…”
Section: Design Planmentioning
confidence: 99%
“…Formation of the desired enaminyl radical cation 5 would then induce an increase in the acidity of the allylic C–H bond, facilitating deprotonation at the β-position. 1a The transiently formed 5pe − species 1 (an intermediate which represents the desired activation mode) should then readily couple with ketyl radical 2 to form the γ-hydroxyketone enamine 6 . Finally, enamine hydrolysis would serve to release the β-union product 7 and regenerate the amine catalyst 3 , thereby completing the organocatalytic cycle.…”
Section: Design Planmentioning
confidence: 99%
See 1 more Smart Citation